The compatibility of osmitic tecnique and vapour equilibrium technique in establishing suction-water content of soil water characteristics curves - Ang, Veei Zhun (2014)
The aim of this study is to establish the soil-water characteristic curve during drying by osmotic and vapour equilibrium techniques and to check the applicability of PEG tested using vapour equilibrium technique principle to establish soil-water characteristics curve without the use of membrane as in the osmotic technique. The establishment of more accurate wide range of suction become of the basic issue in the geotechnical engineering. This study focused on the compatibility of osmotic technique and vapour equilibrium technique in establishing suction-water content of soil water characteristics curves. In order to get more accurate and reliable results, taking a longer time to analyses the soil is much worth then get less accurate result in short time. This studies is conducted using M1X80 bentonite, Speswhite Kaolin, and Greek Bentonite as soil sample for osmotic technique and vapour equilibrium technique based on 5 suction range from 0.44 MPa to 8.17 MPa. The time equilibrium is plot in the beginning of the experiment to identify the end point of the experiment . The final water content of the soil sample is studied and suction-water content soil water characteristic curve is plotted based on 3 soil samples. The compatibility of the each soil sample based on osmotic technique and vapour equilibrium technique is checked and in fact it is not compatible with each other. It can be conclude that the PEG is not applicable in vapour equilibrium technique without the use of the membrane as in the osmotic technique. There is also fungi growth problems occurs when using PEG to applied suction in vapour equilibrium technique at suction lower than 1 MPa.